The Development of Learning Tools for Animalia Concept Based on Guided Inquiry Model in High School Grade X - Anjeli Anjeli; Dharmono Dharmono; Hardiansyah Hardiansyah (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Learning tools are instruments or equipment to carry out the learning process, worksheets, media, methods, and assessment rubric that will be used by the educators and students in their learning activities. This research aims to describe the validity of Model Learning Device Development Guided Inquiry on Animalia Concepts in Class X High School. The method that used in this research is Evaluation Development Research (EDR) through Tessmer Formative Evaluation which is limited only to expert validation. This type of research is a research development to produce products in the form of Syllabus, Lesson plan, worksheet, and valid Teaching Materials. The results showed that: 1) The validity of the syllabus developed based on expert tests has a very valid category, namely 100%, 2) The validity of the lesson plans that are developed based on expert test has a very valid category, namely: 92.19%, 3) Validity of worksheet developed based on test experts have a very valid category, namely 92.5%, and 4) validity on teaching materials developed based on expert tests have very valid category that is 92.56%.AbstrakPerangkat pembelajaran adalah alat atau perlengkapan untuk melaksanakan proses pembelajaran, lembar kerja, media, metode, dan rubrik penilaian yang akan digunakan pendidik dan peserta didik melakukan kegiatan pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan validitas Pengembangan Perangkat Pembelajaran Model Inkuiri Terbimbing pada Konsep Animalia pada SMA Kelas X. Metode penelitian yang digunakan yaitu Evaluation Development Research (EDR) melalui Evaluasi Formatif Tessmer yang dibatasi hanya sampai validasi ahli (Expert Validation). Jenis penelitian ini merupakan penelitian pengembangan untuk menghasilkan produk berupa Silabus, Rencana Pelaksanaan Pembelajaran (RPP), Lembar Kerja Peserta Didik (LKDP), dan Bahan Ajar yang valid. Hasil penelitian menunjukkan bahwa: 1) Validitas terhadap silabus yang dikembangkan berdasarkan uji pakar memiliki kategori sangat valid yaitu 100%, 2) Validitas RPP yang dikembangkan berdasarkan uji pakar memiliki kategori sangat valid yaitu 92.19%, 3) Validitas terhadap LKPD yang dikembangkan berdasarkan uji pakar memiliki kategori sangat valid yaitu 92.5%, dan 4) validitas terhadap bahan ajar yang dikembangkan berdasarkan uji pakar memiliki kategori sangat valid yaitu 92.56%.